Late-Life Exercise and Difficulty with Activities of Daily Living: an 8-Year Nationwide Follow-up Study in Taiwan. Issue 2 (22nd October 2015) - Ku, Po-Wen; Fox, Kenneth R.; Gardiner, Paul A.; Chen, Li-Jung
Abstract: Background: Many studies have shown that low levels of exercise in later life are associated with the progression of difficulties with activities of daily living. However, few have assessed the independent effect of exercise components on difficulty in performing activities of daily living and explored whether the relationship between exercise and activities of daily living is reciprocal. Purposes: This study aimed to examine, in a nationally representative sample of older Taiwanese, the independent effect of the frequency, duration, and intensity of exercise on difficulty with activities of daily living. A secondary objective was to explore the degree to which the relationship of late-life exercise with activities of daily living is bi-directional. Methods: Data from a fixed cohort ( n = 1268, aged 70+) in 1999 with 8 years of follow-up were analyzed. Generalized estimating equation models with multivariate adjustment were performed. Results: Participants engaging in higher levels of exercise had less difficulty with subsequent activities of daily living. Among the components of exercise, only duration, especially 30 min or more per session, was associated with fewer difficulties with activities of daily living. The relationship between exercise and activities of daily living was reciprocal, although the influence of activities of daily living on subsequent exercise levels was weaker. Conclusions: Exercise in later life may be able to minimize the difficulties in activities of daily living and help maintain the mobility and independence of older adults.